Bibliometric analysis for research trends and hotspots in heat and mass transfer and its management of proton exchange membrane fuel cells. (1st March 2023) - Chen, Xin; Zhang, Ying; Xu, Sheng; Dong, Fei
Graphical abstract: Highlights: Bibliometric analysis of heat and mass transfer and its management in PEMFC was carried out. The number of annual publications has experienced a process of increasing, decreasing and increasing. J Power Sources, J Electrochem Soc and Appl Energy are the authoritative journal in this field. Water and heat management needs to be further optimized. Abstract: Heat and mass transfer and its management is an important part of proton exchange membrane fuel cells (PEMFCs), which has a decisive impact on the performance and durability of PEMFCs. In order to comprehend the research progress and hotspots in heat and mass transfer and its management of PEMFC, 3977 literatures related to this field (up to 26th July 2022) were obtained from the Web of Science Core Collection database. Based on the mapping knowledge domain (MKD) and the VOSviewer visualization software, the number of publications, citation frequency, keyword co-occurrence, and clustering were counted and analyzed. The research progress, hotspots, and trends in the field of heat and mass transfer and its management of PEMFC were then summarized. The results show that since 2000, the annual quantity of publications in this field has experienced a period of increasing, decreasing, and then increasing, while in recent years, it is in a period of rapid growth. This field has received extensive attention in China, the United States and Canada, with many researchers, among which the quality of publications from Canada is relatively high. Related studies have been published in energy and electrochemistry journals such as the International Journal of Hydrogen Energy and the Journal of the Electrochemical Society . The Journal of Power Sources is the authoritative journal in this field with the largest total number of publications and total citation frequency. According to the keyword co-occurrence network map, there are four clusters in this field, and each cluster has a different research focus. Among them, cluster 4 has only one keyword, humidification. This field can be roughly divided into three research stages, namely, the exploration of gas–liquid two-phase flow characteristics in PEMFC, the development of PEMFC heat and mass transfer and its management, and the water and heat management and performance optimization of PEMFC. In order to achieve the development goals of high-power density, high reliability and long-life of PEMFC, the research of the third stage should be further deepened in future work. This paper will provide reference for scholars engaged in the field of PEMFC heat and mass transfer and its management.